Intertwined Histories Plants in their Social Contexts - Ellis, Jim (Calgary Institute for the Humanities, 2019)
How do we understand the boundaries of individual creatures? What are the systems of interdependency that bind all living creatures together? Plants were among the the first to colonize the planet. They created the soil and the atmosphere that made life possible for animals. They are some of the largest and oldest life forms on Earth. In spite of their primacy, Western cultures have traditionally regarded plants as the lowest life forms, lacking mobility, sensation, and communication. But recent research argues that plants move and respond to their environment, communicate with each other, and form partnerships with other species. Art, poetry, and essays by cultural anthropologists, experimental plant biologists, philosophers, botanists and foresters expose the complex interactions of the vibrant living world around us and give us a lens through which we can explore our intertwined histories.